Understanding Valuation Convergence in Indian Companies by Comparing Public Vs Private Firms - Bathia, Amit; Aidasani, Diya; Mashru, Dea; Mehta, Dhristi; Zaveri, Harshul; Gupta, Raghav (Asian And Pacific Economic Review, 2025)
With an emphasis on the changing patterns of transparency, liquidity, and investor perception, this study analyzes how firm valuations change as a company transition from private to public ownership (Asker, Farre-Mensa, & Ljungqvist, 2011; Damodaran, 2006; Elnathan, Gavious, & Hauser, 2010). It examines five contemporary Indian companies using a case study methodology: Avenue Supermarts (DMart), HDFC Asset Management Company (HDFC AMC), IndiaMART InterMESH, Computer Age Management Services (CAMS), and Affle (India). Prior to going public between 2017 and 2020, each of these companies was privately held (Nguyen, 2025; Elsedeik, 2024). The study compares valuation metrics like market capitalization, EV/EBITDA, and P/E ratios (in ₹ terms) by looking at six years of financial data before the IPO and at least six years of performance after the IPO. This shows how market discipline changes the value of a company (Fernández, 2007; Livingston, 2014; Harris, Jenkinson, & Kaplan, 2014). According to research, public markets promote data-driven accountability and valuation corrections after financial performance becomes transparent, whereas private valuations frequently place an emphasis on growth narratives and investor optimism (Baker & Wurgler, 2002; Barberis & Shleifer, 2003; Ling, Naranjo, & Scheick, 2010). India's overall shift towards market maturity appears in the findings, which show a consistent trend across sectors: a realignment from perception-driven to performance-based valuations (Varma, 2011; Rath, 2019). According to the study's findings, public valuations define sustainability while private valuations capture ambition. As a result, the transition from private to public ownership is not only a significant financial milestone but also a redefinition of credibility in the process of creating corporate value (Damodaran, n.d.; Shleifer, 2002; Cabral, Mahoney, McGahan, & Potoski, 2019).
ISME
Keywords: Corporate Valuation; Private versus Public Firms; IPO Valuation; Market Efficiency; Enterprise Value; P/E Ratio; EV/EBITDA; Financial Disclosure; Liquidity Premium; Beta; WACC; Indian Capital Markets; Emerging Market Case Study; Behavioral Finance; Valuation